Here's the question you clicked on:
ramuler
|(x-3)(x+2)|=6
|(x-3)(x+2)|=6 means when (x-3)(x+2)<0, -(x-3)(x+2)=6 and when (x-3)(x+2)>=0, (x-3)(x+2)=6
Its easy simply multiply both terms
The method @Neo92 suggested is correct. @ramuler go for it.
answer is A 0, B 1, C 2, D 4
@ramuler it would be great if you try to do it first and if you already tried to solve it, then follow the method Neo suggested.
@ramuler thtz it bro.. as @mathslover said first try it by ur self.. if no luck tell us ur problem